Aktualność myśli i doświadczeń Anieli Godeckiej w świetle współczesnych dylematów ekonomii społecznej - Rutkowska, Anna (Annales. Etyka w Życiu Gospodarczym, 2012)
Aniela Godecka was a co-founder of non-habit Congregation of Little Sisters of Mary Immaculate an active initiator of actions connected with social economy amongst the contemporary factory population. For Aniela Godecka in the sphere of the social economy above all a penetrating analysis and a correct identification of needs of social, professional and economic women were a base of her effective news. Growing disproportions and divisions of the society and the reaction to exclude larger groups from the mainstream of the social life became the base of distinguishing principal areas of Godecka’s activity: service delivery for the society, educational activity, social welfare and health care. Socio-economic transformations taking place throughout the centuries have had a significant impact on the perception of femininity and shaping social mentality. It can therefore pose the question: Whether and to what extent the potential of historical experience Godecka can be used by women 21st century? Godecka’s activity can constitute the inspiration for women living in the 21st century. Aniela Godecka’ experience constitutes the incentive for contemporary women to take part in socio-economic integration, to propagate behaviours and enterprising attitudes and the behaviours in accordance with accepted system of values.